Conolodinines A–D, Aspidosperma–Aspidosperma Bisindole Alkaloids with Antiproliferative Activity from Tabernaemontana corymbosa - Sim, Dawn Su Yin; Navanesan, Suerialoasan; Sim, Kae Shin; Gurusamy, Subramaniam; Lim, Siew Huah; Low, Yun Yee; Kam, Toh Seok (American Chemical Society, 2019)
Examination of the EtOH extract of the leaves of the Malayan Tabernaemontana corymbosa resulted in the isolation of four new (1-4) and two known bisindole alkaloids (5, 6) of the Aspidosperma-Aspidosperma type. The structures of these alkaloids were determined based on analysis of the spectroscopic data (NMR and HRESIMS). X-ray diffraction analyses of the related bisindole alkaloids conophylline (5) and conophyllinine (6) established the absolute configurations. Treatment of the bisindole alkaloid conophylline (5) with benzeneselenic anhydride gave, in addition to the known bisindole polyervinine (7) previously isolated from another Malayan Tabernaemontana, another bisindole product, 8, an isolable tautomer of 7. X-ray diffraction analyses yielded the absolute configurations of both bisindoles and in addition showed that polyervinine (7) exists primarily as the neutral dione structure. The bisindoles (1-8) and the related conophylline-type bisindoles (9-13) showed pronounced in vitro growth inhibitory activity against an array of human cancer cell lines, including KB, vincristine-resistant KB, PC-3, LNCaP, MCF7, MDA-MB-231, A549, HT-29, and HCT 116 cells, with IC50 values for the active compounds in the 0.01-5 μM range. © 2019 American Chemical Society and American Society of Pharmacognosy.